PENGARUH PENGGANTIAN SEBAGIAN RANSUM KOMERSIL DENGAN TEPUNG MAGGOT (Hermetia illucens) TERHADAP KARKAS AYAM BROILER (Gallus dommesticus) - Purnama, Satria Adi; supriyono, supriyono; putra, bela (STOCK Peternakan, 2023)
This study aimed to determine the effect of partial replacement of commercial rations with maggot flour (Hermetia illucens) on the carcass of broiler chickens (Gallus dommesticus). This research was conducted from March 29, 2022 to April 27, 2022 on Jl Kenari Rt 04 Sapta Mulya Village, Rimbo Bujang District, Tebo Regency. The cattle used in this study were 100 DOCs. This study consisted of 5 treatments, namely M0 (without maggot flour), M1 (5% maggot flour + 30% fine bran + 65% commercial ration), M2 (10% maggot flour + 30% fine bran + 60% commercial ration), M3 (15% maggot flour + 30% fine bran + 55% commercial ration), M4 (20% maggot flour + 30% fine bran + 50% commercial rations). The experimental design used in this study was Completely Randomized Design (CRD) with 5 treatments and 4 replications. The parameters observed were absolute carcass weight, breast slice weight, thigh slice weight, back slice weight, and wing slice weight. This study can be concluded that the provision of maggot flour had no significant effect on absolute carcass, breast percentage, thigh percentage, back percentage, and percentage of broiler chicken wings (P0.05). However, it significantly affected the carcass percentage (P0.05) and M4 treatment was the best treatment.